Three-dimensional computed tomography mapping of posterior malleolar fractures - Su, Qi-Hang (World J Clin Cases, 2020)
BACKGROUND: Posterior malleolar fractures have been reported to occur in < 40% of ankle fractures. AIM: To reveal the recurrent patterns and characteristics of posterior malleolar fractures by creating fracture maps of the posterior malleolar fractures through the use of computed tomography mapping. METHODS: A consecutive series of posterior malleolar fractures was used to create three-dimensional reconstruction images, which were oriented and superimposed to fit an ankle model template by both aligning specific biolandmarks and reducing reconstructed fracture fragments. Fracture lines were found and traced in order to generate an ankle fracture map. RESULTS: This study involved 112 patients with a mean age of 49, comprising 32 pronation-external rotation grade IV fractures and 80 supination-external rotation grade IV fractures according to the Lauge-Hansen classification system. Three-dimensional maps showed that the posterior ankle fracture fragments in the supination-external rotation grade IV group were relatively smaller than those in the pronation-external rotation grade IV group after posterior malleolus fracture. In addition, the distribution analyses on posterior malleolus fracture lines indicated that the supination-external rotation grade IV group tended to have higher linear density but more concentrated and orderly distribution fractures compared to the pronation-external rotation grade IV group. CONCLUSION: Fracture maps revealed the fracture characteristics and recurrent patterns of posterior malleolar fractures, which might help to improve the understanding of ankle fracture as well as increase opportunities for follow-up research and aid clinical decision-making.